Priming Issues, Party Visibility, and Party Evaluations: The Impact on Vote Switching. (3rd July 2017) - Geers, Sabine; Bos, Linda
Abstract : Voter volatility has become a hallmark of Western democracies in the past three decades. At the same time short-term factors—such as the media's coverage of issues, parties, and candidates during an election campaign—have become more important for voters' decisions. While previous research did look at how campaign news in general affects electoral volatility in general, it has omitted to explicitly test the mechanisms underlying these effects. Building on theories of agenda setting, (affective) priming, and issue ownership, the current study aims to explain why certain news aspects lead voters to switch their vote choice. We theorize it is the visibility of a party, the evaluation of a party, and the attention for issues owned by a party that primes voters to switch to a certain party. We use national panel survey data ( N  = 765) and link this to an extensive content analysis of campaign news on television and in newspapers in the run up to the 2012 Dutch national elections. The results show that issue news leads to vote change in the direction of the party that owns the issue. Even stronger is the effect of party visibility on vote switching. Our results, however, find the strongest support for the effect of party evaluations on vote change: More favorable news about a party increases switching to that party.